2018
DOI: 10.1016/j.ppees.2018.01.004
|View full text |Cite
|
Sign up to set email alerts
|

Hemiparasite-density effects on grassland plant diversity, composition and biomass

Abstract: Hemiparasitic plants are considered as ecosystem engineers because they can modify the interactions between hosts and other organisms. Thereby, they may affect vegetation structure, community dynamics and facilitate coexistence as they are able to reduce interspecific competition by parasitizing selectively on competitive species and promote subordinate ones. In agri-environmental schemes, introducing the hemiparasite Rhinanthus has therefore been suggested as a low-cost method to increase grassland plant dive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 64 publications
2
24
0
Order By: Relevance
“…If we assume that plant biomass negatively correlates with the light available for bryophytes, our results suggest that an increase in light competition from vascular plants partially explains the negative effect of fertilization on bryophyte diversity. Feßel et al (2016), who measured light transmittance to the ground in German grasslands, found sward cover and aboveground biomasstwo positively related factors (Heer et al, 2018) to be the most important factors explaining lower light levels on the ground, supporting our assumption that higher biomass means less light. Our results indicate that fertilization affects bryophyte diversity through several mechanisms and that the impacts may be more complex than previously thought.…”
Section: Discussionsupporting
confidence: 75%
“…If we assume that plant biomass negatively correlates with the light available for bryophytes, our results suggest that an increase in light competition from vascular plants partially explains the negative effect of fertilization on bryophyte diversity. Feßel et al (2016), who measured light transmittance to the ground in German grasslands, found sward cover and aboveground biomasstwo positively related factors (Heer et al, 2018) to be the most important factors explaining lower light levels on the ground, supporting our assumption that higher biomass means less light. Our results indicate that fertilization affects bryophyte diversity through several mechanisms and that the impacts may be more complex than previously thought.…”
Section: Discussionsupporting
confidence: 75%
“…Parasitism and clonal integration each have strong community‐level effects on their own. For example, through differential effects on hosts and nonhosts and by decreasing the density of vegetation, parasitic plants can change plant community structure (Press & Phoenix, 2005), promote plant species diversity (Grewell, 2008; Heer et al ., 2018), and control invasive plant species (Shen et al ., 2007; Yu et al ., 2008; Cirocco et al ., 2017; Tĕšitel et al ., 2017, 2020; Li et al ., 2019). Clonal integration may modify the response of plants to grazing (Liu et al ., 2020) and help explain why increased dominance by tall, wide‐spreading clonal plants accounts for much of the negative effects of elevated N levels on diversity in some grasslands (Gough et al ., 2012; Dickson et al ., 2014), and why clonal growth in plants is associated with invasiveness (Pyšek et al ., 1995; Pyšek, 1997; Liu et al ., 2006; Song et al ., 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Rhinanthus alectorolophus has a wide range of hosts that includes grasses and legumes (Sandner & Matthies, 2018). The species is used as a tool in restoration of species‐rich grasslands as it reduces competition by grasses and may thus have a positive effect on plant diversity (Bullock & Pywell, 2005; Heer et al, 2018). In all sown plots (four plots per site), ten randomly chosen seedlings of both species were tagged in May 2019 using coloured rings and poles (Appendix ).…”
Section: Methodsmentioning
confidence: 99%